Analysis of Free Text with Omaha System Targets in Community-Based Care to Inform Practice and Terminology Development - Farri, O.; Monsen, K.A.; Westra, B.L.; Melton, G.B. (Applied Clinical Informatics, 2011)
The Omaha system is one of the most widely used interface terminologies for documentation of community-based care. It is influential in disseminating evidence-based practice and generating data for health care quality research. Thus, it is imperative to ensure that the Omaha system reflects current health care knowledge and practice. The purpose of this study was to evaluate free text associated with Omaha system terms to inform issues with electronic health record system use and future Omaha system standard development. Two years of client records from two diverse sites (a skilled homecare, hospice, and palliative care program and a maternal child health home visiting program) were analyzed for the use of free text as a component of the intervention when structured targets for interventions were not identified. Intervention text entries very commonly contained duplicate “carry forward entries”, multiple concepts, mismatched problem focus, or failure to identify an existing appropriate target. Our findings support the need to better address education gaps for clinicians. We identified additional suggested targets for Omaha system problems, and propose new targets for consideration in future Omaha system revisions.
Keywords: Interface terminology; Omaha system; Content coverage; community health care; nursing assessment